COPEWithME: The Role of Parental Ability to Support and Promote Child Resilient Behaviors During the COVID-19 Emergency - Mariani Wigley, Isabella Lucia Chiara; Mascheroni, Eleonora; Bulletti, Francesca; Bonichini, Sabrina (Frontiers in Psychology, 2021)
The COVID-19 pandemic has led to lockdown in many countries and Italy was the first one interested in Europe. The lockdown strategy is an essential step to curb the exponential rise of COVID-19 cases, but it is very demanding for the population involved and especially for children and their families. The aims of the present study were: a) to explore the psychometric properties of the COPEWithME questionnaire, a new tool to evaluate parents’ ability to support and promote child resilient behaviors, b) to investigate the relation between parents’ resilience and their ability to support and promote child resilient behaviors with child resilience and child stress-related behaviors assessed during COVID-19 outbreak. Participants (N = 158 mothers, with 6-to-11 years children, 53% female), who were volunteers and anonymous, filled out an online questionnaire composed by CD-RISC 25, PMK-CYRM-R and COPEWithME. As regard the COPEWithME, Exploratory Factor Analyses revealed a one-factor solution of 18 items. The COPEWithME positively correlates both with mothers’ resilience and with child resilience. Mediation analysis showed that the association between mothers’ resilience and children stress-related behaviors was mediated by mothers’ ability to support and promote child resilient behaviors. The COPEWithME, to our knowledge, is the first measure of parents’ ability to support and promote resilient behaviors in school-age children, a key parenting skill that may help children in dealing with stressful situation as the COVID-19 outbreak. These findings represent useful insights to advance mental health interventions in the post-pandemic phases suggesting focusing on family’s resources and resilience processes.